REDUCTION OF ECOLOGICAL FOOTPRINTS OF DRIFTING FISH AGGREGATING DEVICES (DFADS) USING DRONE TECHNOLOGY IN NIGERIAN OFFSHORE WATERS - Olakunle, G. W.; Falaye, B.; Olabinwonnu, R.; Ayodeji, G. A. (RENEWABLE, 2025)
Drifting Fish Aggregating Devices (dFADs), which are used intensively in industrial tuna fisheries, have become widespread in West African waters. While effective in aggregating pelagic species such as tuna, dFADs have serious environmental consequences in the form of ghost fishing, marine pollution and disruption of ocean ecosystem processes. These challenges are further added to by dFADs drifting into Nigerian offshore waters from neighboring countries, increasing the difficulty of fisheries management and undermining conservation efforts. Existing mitigation efforts are limited by high cost, technology deficits, and weak enforcement capacity. This research examined the possibility of employing drone technology as an affordable and environmentally friendly means of mitigating the environmental impact of dFADs in Nigerian waters. Drone-assisted reconnaissance missions were conducted at three offshore locations — Brass, Escravos and Lagos — augmented by two locally adapted fishery boats. Utilization of drones enabled real-time identification, geolocation, and recovery of errant dFADs, which was more efficient and cost-effective compared to traditional retrieval. The results indicated that drone utilization reduced time and the impacts of uncontrolled dFAD drift, saving marine ecosystems. The research highlighted the need for regional cooperation among ECOWAS member states in the regulation of utilization, traceability and disposal of dFADs through shared surveillance platforms. The outcomes offer actionable suggestions to policymakers, fisheries stakeholders, and conservationists responsible for protecting the marine ecosystem in the Gulf of Guinea, in addition to promoting responsible fishing habits.